COMPUTER ALGORITHMS FOR A FUNDAMENTAL PROBLEM IN BIOINFORMATICS: THE "PROTEIN LOOP CLOSURE" PROBLEM - HING, RATANA (2013)
The "protein loop closure" problem is a fundamental problem in bioinformatics. Thebackbone of a protein is a kinematic chain. When using current techniques to try to get a "picture" of a protein, there are limitations. Whilst we can "see" most ofthe backbone, there are parts that current techniques do not show. We need to fill in any gaps in the "picture", as thebackbone defines thetype of protein. From computational perspective, the "protein loop closure" problem can be viewed as an inverse kinematics problem. Inverse kinematics can be bestthought of in terms of a robotic arm comprising of several links connected by joints.